Job-Hopping Toward Equity - Groysberg, Boris; Groysberg, Boris; Healy, Paul; Lin, Eric (MIT Sloan Management Review, 2021)
Changing employers has been linked to larger pay increases for executives and managers. Although survey-based studies suggest that men gain more than women, an analysis of more than 2,000 job moves found that executive women are commanding bigger increases than men when switching employers. In certain contexts, female executives can use these external moves to increase their own compensation and perhaps narrow the gender pay gap overall.